PEMBUATAN GAS HIDROGEN DARI LIMBAH ALUMINIUM KALENG SOFT DRINK MENGGUNAKAN KATALIS KALIUM HIDROKSIDA (KOH) - Selviana Selviana; Indah Purnamasari; Robert Junaidi (Jurnal Daur Lingkungan, 2026)
Cans of soft drinks are a source of waste in Indonesia, as this inorganic waste cannot be decomposed rapidly and naturally. Aluminum takes about 400 years to decompose in the soil. A large amount of aluminum contained in the cans can be reused as goods or raw materials to produce hydrogen gas. Hydrogen is considered an environmentally friendly fuel regarding its very low emissions and high energy value. The hydrogen gas production process involves a reaction between aluminum metal and a catalyst. In this case, the use of a strong base catalyst such as KOH has been shown to produce more hydrogen. This experiment aims to utilize the cans as a material to produce hydrogen gas. This experimental process was carried out by reacting aluminum metal powder sourced from used drinking cans with varying aluminum masses of 3, 4, 5 and 6 g with water and KOH catalysts of 2, 3 and 4 M in a fixed bed reactor, with a process for 20 minutes at a temperature of 50 °C. The results of the reactions were analyzed using a Gas Detector Analyzer. This study shows that 6 g of aluminum catalyzed with 4 M KOH results in 66% Hydrogen gas, and 3 g of aluminum catalyzed with 2 M KOH results in 20% Hydrogen gas. This proves that increasing the amount of mass and concentration in the process increases the resulting volume of hydrogen gas.